Depositor Behavior under Macroeconomic Risk: Evidence from Bank Runs in Emerging Economies - Levy-Yeyati, Eduardo; Martinez Peria, Maria Soledad; Schmukler, Sergio L. (2012)
Depositor behavior has been associated with bank-specific characteristics, random runs, or contagion episodes. Using evidence on the 2000-02 bank runs in Argentina and Uruguay, this paper shows that macroeconomic risk is also important. Few macroeconomic shocks can quickly cause large runs. Macroeconomic risk affects deposits regardless of traditional bank-specific characteristics. Furthermore, bank exposure to macroeconomic factors can explain differences in deposit withdrawals. During crises, the evolution of bank-specific characteristics is mainly driven by macroeconomic factors, while the informational content of bank-specific variables declines. Overall, depositors seem responsive to risk in a broader sense than that often considered by the literature.